Near-infrared Fluorescent Divalent RGD Ligand for Integrin α(v)β(3)-targeted Optical Imaging - Ye, Yunpeng (2012)
A new near-infrared fluorescent compound containing two cyclic RGD motifs, cypate-[c(RGDfK)](2) (1), was synthesized based on a carbocyanine fluorophore bearing two carboxylic acid groups (cypate) for integrin α(v)β(3)-targeting. Compared with its monovalent counterpart cypate-c(RGDfK) (2), 1 exhibited remarkable improvements in integrin α(v)β(3) binding affinity and tumor uptake in nude mice of A549. The results suggest that cypate-linked divalent ligands can serve as an important molecular platform for exploring receptor-targeted optical imaging and treatment of various diseases.